A contribuição do trabalho de campo como facilitador do processo de ensino-aprendizagem da geografia - Nascimento, Pâmela Farias Oliveira do (Universidade Federal do Tocantins, 2019)
Fieldwork is an essential tool in the teaching / learning process. With the development of the present research, it can be affirmed that fieldwork is a facilitator of the teaching/ learning process in Geography. It gives room for the content studied in the classroom, can be viewed in the environment in an empirical and practical way. Thus, it makes possible the narrowing of the relationship between theory and practice. With the objective of comparing the school units of Colégio Estadual Marechal Artur da Costa e Silva and Escola Família Agrícolade Porto Nacional - TO, we carried out an investigation of how the field work with the students of the schools occurs, and the relation of the Referencial das Escolas Públicas do Estado do Tocantins with theory and practice in the teaching of Geography, as well as if the textbooks adopted by the schools include information about the field work and how it is presented. In order to complete a successful fieldwork, it was verified that there is a need to follow criteria for its accomplishment, following a protocol of procedures: the preparation, the realization and the results / evaluation. Although the Referencial das Escolas Públicas do Estado do Tocantins and the textbooks adopted by the schools are silent and deficient in the proposal of the field work, the teachers of the two schools proposed the classes the field work and emphasized their importance in aid of the assimilation and fixation of the contents discussed in the classroom. Such a practice adopted by teachers was scarce in the lack of resources, investments, beyond the theoretical basis in the bibliographical references to be scarce for the procedures and orientations in the execution of the fieldwork in the teaching / learning in Geography. Students recognize the need to do the fieldwork and are willing to do the practice of the activity, even if they are aware of the limitations faced during the study period.